Immune-suppression by OsHV-1 viral infection causes fatal bacteraemia in Pacific oysters. Issue 1 (December 2018) - Lorgeril, Julien; Lucasson, Aude; Petton, Bruno; Toulza, Eve; Montagnani, Caroline; Clerissi, Camille; Vidal-Dupiol, Jeremie; Chaparro, Cristian; Galinier, Richard; Escoubas, Jean-Michel; Haffner, Philippe; Dégremont, Lionel; et al.
Abstract Infectious diseases are mostly explored using reductionist approaches despite repeated evidence showing them to be strongly influenced by numerous interacting host and environmental factors. Many diseases with a complex aetiology therefore remain misunderstood. By developing a holistic approach to tackle the complexity of interactions, we decipher the complex intra-host interactions underlying Pacific oyster mortality syndrome affecting juveniles ofCrassostrea gigas, the main oyster species exploited worldwide. Using experimental infections reproducing the natural route of infection and combining thorough molecular analyses of oyster families with contrasted susceptibilities, we demonstrate that the disease is caused by multiple infection with an initial and necessary step of infection of oyster haemocytes by theOstreid herpesvirus OsHV-1 µVar. Viral replication leads to the host entering an immune-compromised state, evolving towards subsequent bacteraemia by opportunistic bacteria. We propose the application of our integrative approach to decipher other multifactorial diseases that affect non-model species worldwide. Pacific oyster mortality syndrome is a poorly understood cause of mortality in commercially important oyster species. Here, the authors use multiple infection experiments to show that the syndrome is caused by sequential infection by herpesvirus and opportunistic bacteria.